Pelatihan Pengelolaan Keuangan dan Pelatihan Pemasaran Digital pada Kedai Kopi Garasi - Kareja, Novilia; Setiadevi, Shinta; Alfiyah, Nurul; Triyaningsih, Lulus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The aim of this program to the Garage Coffee Shop is carried out as part of an effort to support the development of MSMEs, especially in dealing with financial problem, digital marketing, and product development. This activity is carried out in several methods including interviews and discussions, training and pratices of financial management, marketing and product development, and mentoring as final stage. The results of these activities are in the form of capacity building by partners and related to financial management using applications, partners have canvas-based websites and new product variants. The results of this service can be realized because of the active participation and participation of partners. Partners are expected to be consistent in carrying out financial records and business development.